The Learning Routines for SD/MI Level in terms of the Impact Covid-19 Pandemic (Case study at MI Al-Muhajarin Latukan Karanggeneng Lamongan) - Syaipudin, Latif; Nurfajriya Awwalin, Idah (CV. Media Publikasi Profesional, 2021)
The education is a necessity for the development of a country, routine learning models are important in the implementation of learning. This study aims to examine the extent to which learning routines were carried out during the Covid-19 pandemic. This research is a qualitative research with a case study approach, the data collection techniques used are interviews and observation. The results of the study indicate that routine is an important thing in learning activities at the SD / MI level. In accordance with the results of this study with comparisons of routines carried out before the Covid-19 pandemic, this can be an example of the implementation of learning carried out during the Covid-19 pandemic or after. Basically, the main foundation in the learning process is by implementing routine learning, with the hope carried out will give maximum results.